SOCIAL OPPRESION IN MULK RAJ ANAND’S UNTOUCHABLE - Wirayana Sipayung; Rosa Maria Simamomora (Muse: Jurnal of Art, 2022)
This is a study of Mulk Raj Anand’s Untouchable as the representation of social oppression. The novel shows that social oppression is felt as the impacts of poverty and stigmatization. This is library research and applies mimetic theory proposed by M.H. Abrams. Mimetic approach looks literary work as the imitation of natural aspects and replication of world life. The oppression which is represented by outcast characters feel oppressed because they do not have access to public facilities, education, health service, and job. They are not allowed to use public facilities such as well, temple, road, and get good job because they are poor, considered virus and cursed. They become the victims of stigmatization, prejudice, exile, and hatred